Flood impact on masonry buildings: The effect of flow characteristics and incidence angle. (July 2019) - Postacchini, Matteo; Zitti, Gianluca; Giordano, Ersilia; Clementi, Francesco; Darvini, Giovanna; Lenci, Stefano
Abstract: Climate change and the raising number of extreme events, such as severe floods, has increased the attention on their effects on urban systems. Urban floods generate important hydrodynamic loads on building and this work proposes a first systematic study on the actions generated by floods with different characteristics (depth, velocity and incidence angle) on masonry buildings. The study is carried out with experimental tests reproducing a masonry bay with scale 1:10, while the effect of the flow hitting the building has been obtained by moving the building in the water at rest. The pressure generated by the fluid at the four walls of the building was recorded using pressure transducers. It has been found that the overpressure acting on the building depends on the flow characteristics in different manner for the frontal, lateral and rear walls. Further, the incidence angle plays a major role in the generation of a pressure gradient along the impacted wall, and significantly affects both peak frequency and spectral energy. Use of theoretical models suggests that (i) the drag coefficient of the building decreases with the Froude number, and only slightly depends on the incidence angle, and (ii) the blocking effect largely affects the hydrodynamics around the structure.